2018
DOI: 10.1002/ijgo.12586
|View full text |Cite
|
Sign up to set email alerts
|

Transient reduction in abortion‐related lethality after interventions to reduce delays in provision of care at Centre Hospitalier de Libreville, Gabon

Abstract: Abortion‐related fatalities decreased from 12.3 per 1000 abortions to 0.7 per 1000 following an intervention at the Centre Hospitalier de Libreville, Gabon. After discontinuation of the intervention, fatalities reverted to previous levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…It is a quick procedure that can be performed in outpatient clinics using less complex anesthetic procedures [8,13]. It has been emphasized that the replacement of uterine curettage by MVA reduces the mortality rate from 1.23-0.07% [24]. A systematic review that analyzed complications related to MVA showed that less than 5% of women experienced hemorrhage without blood transfusion, less than 0.1% presented with uterine perforation or bleeding requiring blood transfusion, less than 0.5% were hospitalized, and only 3% had repeated aspirations, with no maternal deaths reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is a quick procedure that can be performed in outpatient clinics using less complex anesthetic procedures [8,13]. It has been emphasized that the replacement of uterine curettage by MVA reduces the mortality rate from 1.23-0.07% [24]. A systematic review that analyzed complications related to MVA showed that less than 5% of women experienced hemorrhage without blood transfusion, less than 0.1% presented with uterine perforation or bleeding requiring blood transfusion, less than 0.5% were hospitalized, and only 3% had repeated aspirations, with no maternal deaths reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…Between 1989 and today. This has gone from endouterine curettage under general anesthesia to manual suction [16,18]. At the Libreville University in 2005, the proportion of manual suction carried out was 1.7%.…”
Section: Supportmentioning
confidence: 99%
“…At the Libreville University in 2005, the proportion of manual suction carried out was 1.7%. In 2016 it rose to 64.5% and in other countries which have adopted the IFGO initiative it also increased [18]. These figures are below those of Moussa Nouhoum in Ségou (97.1%) and Leke and Tumasang in Cameroon (100%) [7,12,19].…”
Section: Supportmentioning
confidence: 99%